A prediction model for successful anticoagulation in cirrhotic portal vein thrombosis. Issue 1 (January 2019) - Rodriguez-Castro, Kryssia I.; Vitale, Alessandro; Fadin, Mariangela; Shalaby, Sarah; Zerbinati, Patrizia; Sartori, Maria Teresa; Landi, Stefano; Pettinari, Irene; Piscaglia, Fabio; Han, Guohong; Burra, Patrizia; Simioni, Paolo; et al.
Abstract : Background and objective: Portal vein thrombosis (PVT) is a common complication in cirrhosis, and when complete, it increases morbidity and mortality in liver transplant candidates. The aim of the study was to assess the hemostatic status, as well as clinical characteristics of thrombus and patients, as predictors of therapeutic efficacy of anticoagulation for the treatment of PVT in cirrhotics. Patients and methods: Patients with cirrhosis consecutively treated for PVT with enoxaparin were enrolled. All patients underwent evaluation of coagulation status and thrombophilia screening. Thrombus characteristics and extension were evaluated at baseline and during follow-up. Anticoagulation was continued until recanalization or up to 12 months. Variables correlated with the response to anticoagulation were used to create a predictive score that was validated in an external multicenter cohort. Results: A total of 65 patients were included and had partial PVT in most cases (72%). Treatment with enoxaparin resulted in an overall response rate of 66% (43/65) after a median time of 4.4 months and 76% (33/43) within the first 6 months. At multivariate analysis, efficacy of anticoagulation correlated with the severity of liver disease, complete verus partial PVT, age of the thrombus, and time interval from treatment start (<6 months). The areas under the curve of the statistical model for predicting the response to anticoagulation were 0.84 and 0.76 for the training ( n =65) and validation ( n =60) cohorts, respectively. Conclusion: Early diagnosis and early treatment are key factors for the successful management of PVT in cirrhosis, so that screening of PVT and prompt start of anticoagulant treatment should be mandatory. Abstract : Supplemental Digital Content is available in the text.